Workplace Stress in the Era of Digital Transformation: A Psychological Approach to Employee Well-Being - Akbar, Muhammad Aliyandri; Varias, Vina; Risa, Tiara Dean; Bhirawa, Madyastha Aji; Nugraha, Risman (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
Digital transformation has fundamentally reshaped the world of work, bringing both significant opportunities and psychological challenges for employees. The massive integration of digital technologies, ranging from artificial intelligence to ubiquitous connectivity, has given rise to new forms of workplace stress such as technostress, cognitive overload, and digital presenteeism. These challenges are further intensified by the “always-on culture,” which blurs the boundaries between work and personal life, thereby increasing the risk of burnout, mental fatigue, and declining job satisfaction. This study aims to comprehensively examine the psychological mechanisms underlying the relationship between digital transformation and employee well-being, while also identifying organizational strategies to mitigate its adverse impacts. The research employs a literature review method by analyzing recent academic sources from 2020 to 2025, obtained from international databases such as Scopus, Web of Science, and PsycINFO. Thematic analysis was conducted to identify patterns, themes, and emerging trends related to workplace stress in digital contexts. The findings reveal that digitalization escalates multitasking demands, job uncertainty, and reduced employee autonomy, ultimately undermining psychological well-being. Nevertheless, organizational support, digital literacy, and effective work–life balance policies are shown to reduce these psychological burdens. This study emphasizes the importance of psychology-based interventions, digital leadership oriented toward well-being, and adaptive stress management programs that align with the dynamics of digital work. The implications of this research are significant for the development of industrial–organizational psychology theory as well as human resource management practices, particularly in fostering healthier work environments amid the ongoing digital transformation.